ANALISIS PENDAPATAN PETANI PENYADAP GETAH PINUS DI DESA TANGKULOWI KECAMATAN KULAWI KABUPATEN SIGI SULAWESI TENGAH - Suwaji, Sugianto; Lamusa, Arifuddin; Howara, Dafina (AGROTEKBIS, 2017)
This research aims to know the farmer income of pine SAP tappers in the village of Tangkulowi sub-district of Kulawi, Sigi Regency. Determination of the respondents in this research was conducted by the census method, that is taken from the population. The population in this study was as many as 42 people tappers and it was taken samples as many as 42 people as well. Methods of analysis used was the income analysis.The results of the analysis showed that the income earned byfarmers of pine SAP tappers in the village of Tangkulowi sub-district of Kulawi Sigi Regency was Rp. 2,157,403.18 per harvesting season or Rp. 3,082,004.54 for a month. The income average per season of pine SAP tappers farmers harvest was obtained for three weeks. Earned income of farmers of pine SAP tappers in the village of Tangkulowi sub-district of Kulawi Regency Sigi quite large that is reached Rp. 3,082,004.54 per a month that means it is greater than the Provincial Minimum Wage (UMP) of Central Sulawesi 2016 was Rp. 1,670,000 for a month. Key Words : Acceptance of farmers, Farmers income and Revenue analysis